Hubungan Penggunaan Instagram dengan Pemenuhan Kebutuhan Informasi Warga Dayeuhkolot Kabupaten Bandung - Ristianto; Rini Rinawati (Bandung Conference Series: Communication Management, 2024)
Abstract. This research is entitled The Relationship between Instagram Use and Fulfilling the Information Needs of Dayeuhkolot Residents, Bandung Regency "Correlational Study of the Instagram Account @Infotidayeuhkolot". The purpose of this research is to find out how much influence the social media Instagram has on the information needs of the community, especially residents around the Dayeuhkolot area. This research uses the uses and gratifications theory, where this theory emphasizes that listeners, readers, viewers can choose and use various media options such as Instagram social media as a determinant of selecting messages and media for personal satisfaction. The description of this theory is that media is directly related to active audiences, such as Instagram social media as a provider of information that can be accessed by Instagram users. This research uses quantitative methods with a correlational approach. The population in this study were Instagram followers @infotidayeuhkolot with a sample of 51 respondents. Meanwhile, the data collection technique for this research was carried out through distributing questionnaires and observation. The results of this research are: (1) There is a positive relationship between aspects of the intensity of Instagram media use and fulfilling information needs. (2) There is a positive relationship between aspects of message content using Instagram media and fulfilling information needs. (3) There is a positive relationship between the attractiveness aspect of using Instagram media and fulfilling information needs. Keywords: Social Media, Instagram, Information Needs. Abstrak. Penelitian ini berjudul Hubungan Penggunaan Instagram Dengan Pemenuhan Kebutuhan Informasi Warga Dayeuhkolot Kabupaten Bandung “Studi Korelasional Pada Akun Instagram @Infotidayeuhkolot”. Tujuan diadakan penelitian ini adalah untuk mengetahui seberapa besar pengaruh dari media sosial instagram terhadap kebutuhan informasi masyarakat, terutama warga di sekitar daerah Dayeuhkolot. Penelitian ini menggunakan teori uses and gratifications, dimana teori tersebut menekankan bahwa pendengar, pembaca, penonton dapat memilih dan menggunakan opsi berbagai media seperti halnya media sosial instagram sebagai penentu pemilihan pesan dan media untuk kepuasan pribadi. Gambaran teori ini media berkaitan langsung dengan khalayak aktif, seperti halnya media sosial instagram sebagai penyedia informasi yang dapat diakses oleh pengguna instagram. Penelitian ini menggunakan metode kuantitatif dengan pendekatan korelasional. Populasi dalam penelitian ini adalah followers instagram @infotidayeuhkolot dengan sampel sebanyak 51 responden. sedangkan Teknik pengambilan data penelitian ini dilakukan melalui penyebaran angket dan observasi. Hasil dari penelitian ini adalah: (1) Terdapat hubungan positif antara aspek intensitas penggunaan media instagram dengan pemenuhan kebutuhan informasi. (2) Terdapat hubungan positif antara aspek isi pesan penggunaan media instagram dengan pemenuhan kebutuhan informasi. (3) Terdapat hubungan positif antara aspek daya tarik penggunaan media instagram dengan pemenuhan kebutuhan informasi. Kata Kunci: Media Sosial, Instagram, Kebutuhan Informasi.